Molecular Docking of Hygrophila auriculata (Schum.) Heine Compounds Targeting PBP2 Protein in Neisseria gonorrhoeae - Salmasfattah, Novyananda; Prayogi, Syaiful; Prasetyawan, Fendy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Antibiotic resistance in gonorrhoea cases and patients is detrimental. Amidst the rising cases of gonorrhoea caused by Neisseria gonorrhoeae, Hygrophila auriculata (Schum.) Heine has activity as an antibiotic for the disease. The penicillin-binding protein 2 (PBP2) is a transpeptidase that catalyses the formation of cross-bridges on bacterial cell wall peptidoglycan, which will be the target of this plant. The purpose of molecular docking study is to see the binding affinity, compounds in Hygrophila auriculata (Schum.) Heine and ceftriaxone which is used as a comparison drug, will be targeted at PBP protein. Discovery studio visualizer v21.1.0.20298 was used for PBP2 protein preparation and visualisation. DoG Site Scorer was used to predict ligand binding sites on PBP2 proteins. PyRx 0.8 was used for virtual screening, validating of the docking method, and ligand preparation. Compounds in Hygrophila auriculata (Schum.) Heine as ligands were derived from MPDB 2.0 and the following PubChem codes; apigenin CID 5280443, luteolin CID 5280445, allagic acid CID 5281855, gallic acid CID 370, quercetin CID 5280343, lupeol CID 259846, lupenone CID 92158, betulin CID 72326, stigmasterol CID 5280794, and comparator drug ceftriaxone CID 447043. The binding affinity of ellagic acid -9,8 from Hygrophila auriculata (Schum.) Heine was lower than ceftriaxone -9,4 on the target PBP2 protein. Some of the amino acid residues that appear in protein-ligand docking include: ALA A:310, THR A:500 and 347, LYS A:313, and SER A:362. These amino acid residues owned by the PBP2 protein serve as the bonding bridge. Ellagic acid, the compound has potential as an antibiotic in gonorrhoea. Further testing and studies are needed to strengthen the evidence of the findings in this study